2008
DOI: 10.1159/000170903
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Genotyping of an Infectious Pancreatic Necrosis Virus from Asymptomatic Rainbow Trout <i>(Oncorhynchus mykiss)</i> Facilities in Mexico

Abstract: Background: Infectious pancreatic necrosis virus (IPNV) is a birnavirus that causes a lethal disease in both hatchery-reared juvenile salmonids and other non-salmonid fishes. IPNV has been classified into seven genogroups based on the analysis of the VP2/NS junction region of the viral A RNA segment. Methods: Ten organisms from two trout-rearing farms were used for viral isolation in RTG-2 cells. Cells were inoculated with samples from spleen, kidneys and pyloric caeca. The viral isolate was initially identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 62 publications
1
10
0
Order By: Relevance
“…Phylogenetic analysis confirmed the six genogroups reported by Blake et al (2001aBlake et al ( , 2001b) and a seventh by Nishizawa et al (2005), with the GenBank IPNV sequences being grouped as previously reported. Previous studies of the partial sequences of the VP2 gene of Mexican IPNV isolates, such as Guerrero et al (2008) and Barrera et al (2011), reported findings similar to those of the present work, placing the Mexican isolates in genogroup 1 and determining that they are closely related to the highly characterized American Buhl strain (Ortega et al 2002;Barrera et al 2011). The greatest number of highly characterized IPNV isolates is from genogroup 1, which consists primarily of isolates from the USA and Canada.…”
Section: Discussionsupporting
confidence: 86%
“…Phylogenetic analysis confirmed the six genogroups reported by Blake et al (2001aBlake et al ( , 2001b) and a seventh by Nishizawa et al (2005), with the GenBank IPNV sequences being grouped as previously reported. Previous studies of the partial sequences of the VP2 gene of Mexican IPNV isolates, such as Guerrero et al (2008) and Barrera et al (2011), reported findings similar to those of the present work, placing the Mexican isolates in genogroup 1 and determining that they are closely related to the highly characterized American Buhl strain (Ortega et al 2002;Barrera et al 2011). The greatest number of highly characterized IPNV isolates is from genogroup 1, which consists primarily of isolates from the USA and Canada.…”
Section: Discussionsupporting
confidence: 86%
“…In Mexico, epidemiological studies identified IPNV by the principal national zones of production of rainbow trout [17,21], and in 2009 was reported a prevalence of 11.90% [21]. Genotyping and phylogenetic studies by VP2 gene from Mexican IPNV isolates have been performed [2,7,22], however its biological virulence is unknown. The objective of the present study was to determine the virulence of Mexican isolates in rainbow trout fry and related the results to VP2 amino acid fingerprint of the virus.…”
mentioning
confidence: 99%
“…Subsequent work reported the presence of IPNV in other states within Mexico (Ortega et al 2007). One of these was analyzed and assigned to genogroup I along with the West Buxton and JasperD strains (Guerrero et al 2008), thus sharing the same branch of the phylogenetic tree as the first Mexican isolate (Ortega et al 2002). However, considering that Mexico traditionally has been dependent on the importation of rainbow trout eggs from various countries to meet domestic demand, we can expect that some of the isolates obtained will correspond to different genogroups, as has been reported in other countries (Heppell et al 1992;Cutrin et al 2004).…”
mentioning
confidence: 99%